1992
DOI: 10.1002/joc.3370120303
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and subseasonal patterns of the long‐term trends of Indian summer monsoon rainfall

Abstract: Long-term changes in the Indian monsoon rainfall on regional and local scales have important social and economic consequences. To present a comprehensive picture of such changes, the monthly rainfall data at 306 stations, well spread over India, have been analysed over 114 years (1871-1984), for long-term trends. The trends are quantified by linear trend for monthly as well as seasonal rainfall for each station. Some broad contiguous areas showing statistically significant trends have been identified. Areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
90
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(102 citation statements)
references
References 18 publications
12
90
0
Order By: Relevance
“…However, the inter-correlations among the individual months are insignificant. Similar features were also observed in the earlier study for the Indian summer monsoon by Rupa Kumar et al (1992). This suggests that the intra-seasonal oscillations are present within the season and they have significant influence on the inter-annual variability of seasonal NWIWP.…”
Section: Subseasonal Inter-correlation Of Nwiwpsupporting
confidence: 89%
“…However, the inter-correlations among the individual months are insignificant. Similar features were also observed in the earlier study for the Indian summer monsoon by Rupa Kumar et al (1992). This suggests that the intra-seasonal oscillations are present within the season and they have significant influence on the inter-annual variability of seasonal NWIWP.…”
Section: Subseasonal Inter-correlation Of Nwiwpsupporting
confidence: 89%
“…Rainfall decline is more predominant in the months of June and July but not so in August and September. The decreasing variability in southwest monsoon rainfall over Kerala is supported by other researchers [26,16]. The decline in frequency of the weather systems in recent years over the peninsula may be an important reason for the reduction in southwest monsoon rainfall over Kerala.…”
Section: Variability In Annual and Seasonal Rainfallsupporting
confidence: 62%
“…Since rainfall is having high spatial variability, existence of long-term trend in smaller spatial scale was already reported by Koteswaram and Alvi (1969), Jagannathan and Parthasarathy (1973), Jagannathan and Bhalme (1973). In the subdivisional scale, existence of trends was noticed by Parthasarathy (1984) and Rupa Kumar et al (1992). The study by Parthasarathy (1984) suggested that monsoon rainfall over two subdivisions viz.…”
Section: Introductionmentioning
confidence: 76%
“…Punjab, Konkan and Goa, West Madhya Pradesh and Telangana showed increasing trends. However, Rupa Kumar et al (1992) considered the linear trend analysis of each of the 306 stations of the IITMS and studied their spatial pattern. They have found significant increasing trend in monsoon seasonal rainfall along the west coast, north Andhra Pradesh and northwest India while significant decreasing trends over east Madhya Pradesh and adjoining areas, north-east India and parts of Gujarat and Kerala.…”
Section: Introductionmentioning
confidence: 99%